Underage drinking: prevalence and correlates of risky drinking measures among youth aged 12–20. (3rd July 2016) - Richter, Linda; Pugh, Brandie S.; Peters, Elizabeth A.; Vaughan, Roger D.; Foster, Susan E.
ABSTRACT: Background : Underage drinking and its effects have been researched extensively. However, no study to date has examined how the levels of drinking that have been defined as risky for adults might relate to youth who have a heightened physiological vulnerability to alcohol. Objectives : To examine a range of drinking measures that go beyond common measures of youth alcohol use to gain a more detailed understanding of the nature of underage drinking and its associated correlates and outcomes. Methods : Analyzing data from a 2013 nationally representative US survey, we examined a variety of measures of alcohol use among 24, 445 youth (weighted N = 381, 155, 562), the demographic groups most likely to have reported drinking in these ways, and associations between these measures of drinking and a number of adverse outcomes. Results : On all measures of potentially risky drinking, including meeting diagnostic criteria for an alcohol use disorder, underage drinkers exceeded the rates found for adults. Independent of sex, race, and age, youth who reported drinking in ways that exceeded guidelines set for adults had increased odds of meeting diagnostic criteria for an alcohol, tobacco, or other drug use disorder, and of reporting a number of health problems. Conclusions : The high rates at which youth report engaging in a range of risky drinking behaviors suggest a need for a more nuanced approach to substance use and mental health screening and interventions in clinical practice. The findings also underscore the need to address apparent misconceptions about what constitutes unhealthy or unsafe alcohol use among youth.